2021
DOI: 10.1096/fj.202101401rr
|View full text |Cite|
|
Sign up to set email alerts
|

Choline metabolome response to prenatal choline supplementation across pregnancy: A randomized controlled trial

Abstract: Pregnancy places a unique stress upon choline metabolism, requiring adaptations to support both maternal and fetal requirements. The impact of pregnancy and prenatal choline supplementation on choline and its metabolome in free-living, healthy adults is relatively uncharacterized. This study investigated the effect of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Ischemic and non-ischemic cortical brain tissue from offspring was measured for acetylcholine, betaine, choline, glycerophosphocholine, methionine, phosphocholine, phosphatidylcholine, and sphingomyelin levels using the LC-MS method as previously reported (26, 27).…”
Section: Methodsmentioning
confidence: 99%
“…Ischemic and non-ischemic cortical brain tissue from offspring was measured for acetylcholine, betaine, choline, glycerophosphocholine, methionine, phosphocholine, phosphatidylcholine, and sphingomyelin levels using the LC-MS method as previously reported (26, 27).…”
Section: Methodsmentioning
confidence: 99%
“…While we compared 2 doses of supplemental choline, informed by previously observed cognitive benefits ( 14 ), we did not have a third intermediate group to assess the dose–response relation between choline supplementation and DHA outcomes. Additionally, while our isotopic enrichment data support a clear role for the PEMT pathway metabolites in improving DHA status, there are notable nuances to the interpretation of the labeled choline metabolome in the context of an intervention that alters endogenous pool sizes across pregnancy, a physiological state that violates steady state assumptions, which we have detailed elsewhere ( 27 ).…”
Section: Discussionmentioning
confidence: 60%
“…Participant adherence to the study protocol was >99%, based on the number of returned juice containers (containing the choline supplement) and the number of returned DHA capsules. Further, mean concentrations of plasma free choline, which have been shown to be responsive to choline supplementation during pregnancy ( 10 ), were significantly higher in this cohort in the choline intervention (vs. control) group, with between-group differences detected at visit 2, visit 3, and delivery ( 27 ).…”
Section: Resultsmentioning
confidence: 79%
“…During pregnancy and lactation, the mother transmits choline to offspring through the placenta and breast milk 24 . Many studies have found that choline supplementation during the embryonic period can not only improve the cognitive ability of the adult brain, but also advance the cognitive development of the brain 25,26 . Specifically, Moreno et al found that prenatal choline supplementation could accelerate the development of long‐term memory in offspring rats 27 .…”
Section: Introductionmentioning
confidence: 99%
“…24 Many studies have found that choline supplementation during the embryonic period can not only improve the cognitive ability of the adult brain, but also advance the cognitive development of the brain. 25,26 Specifically, Moreno et al found that prenatal choline supplementation could accelerate the development of long-term memory in offspring rats. 27 Moreover, Johns et al reported that choline supplementation alleviated chemotherapeutic-induced spatial memory deficits.…”
Section: Introductionmentioning
confidence: 99%